Self-Report Measures Assessing Aspects of Personal Recovery in Relatives and Other Informal Carers of Those With Psychosis: A Systematic Review - Hilton, Claire; Jones, Steven; Akers, Nadia; Panagaki, Katerina; Sellwood, William (Frontiers in Psychology, 2022)
Background: Providing long-term care for a family member with psychosis can cause significant distress for carers due to the trauma of seeing their loved one in crisis, dealing with the difficult symptoms of psychosis and the burden of providing care. An important aspect of carers’ adjustment can be construed as their personal recovery in relation to having a relative affected by psychosis. Self-report measures are increasingly used to assess personal recovery in service users, but less is known about the utility of such tools for carers. Aims: This review aimed to identify all self-report measures assessing aspects of carers’ personal recovery, and to quality appraise them. Methods: Academic Search Ultimate, CINAHL, MEDLINE, PsychINFO and PubMed were searched for articles that reported the development of self-report measures created for carers of those with psychosis. Studies were appraised using the COnsensus-based Standards for the Selection of health status Measurement INstruments (COSMIN) checklist. A Levels of Evidence synthesis provided overall quality scores for each measure. Results: The search identified 3,154 articles for initial screening. From a total of 322 full text articles, 95 self-report measures were identified with a final 10 measures included for the quality assessment showing varying levels of psychometric rigor. Conclusions: The results show that no single self-report measure is currently available for use to comprehensively assess personal recovery for carers, highlighting the need for further research in this area and the development of a new measure.